A implantação de estratégias de responsabilidade social por EMNEs em países em desenvolvimento na visão de diferentes grupos de interesse casos (África e América Latina em Moçambique) - Mateço, Raimundo Alfândega (2016)
The main objective of this Thesis is to analyze, in the view of different stakeholders, the strategies of social responsibility of emerging multinational companies in developing countries. Thus, the specific objectives are the following:(i) describe the corporate social responsibility strategy of A, and of B in Mozambique; (ii) analyze the vision of the Community and Local Government; and (iii) propose actions to improve the performance of companies within the social responsibility in Mozambique. The Thesis was guided through the following methodology: (i) primary data collection (interviews involving the Government, the Companies, and the Community members), from twenty (20) informants in Tete and Maputo provinces; (ii) triangulation between primary data and secondary data (reports, magazines); (iii) analysis and interpretation of data on each company (A and B); (iv) analysis and comparative interpretation of the data on the two companies. The results indicate that, to date, the A company complied with the social responsibility actions through: a) construction of a building for the operation of a police station; b) offering of jobs for local people; c) support for schoolage children in school supplies; d) support for community through mosquito nets to combat diseases such as malaria; e) support to the community in the construction of improved housing; f) road construction; g) support to the community in baskets of food, and some tools and products for cultivation; h) sealing the local cemetery; i) construction of a hospital, and providing a doctor. In turn, B fulfilled the social responsibility actions through: a) village electrification; b) construction of roads; c) supply of drin king water; d) offering of jobs to the community; e) improving the health, education and housing; f) increased levels of business and entrepreneurship in the community. However, on a comparative analysis of the integration companies in the communities, we found that, with respect to A, despite some negative aspects such as: a) inefficiency in the supply of water to the community; b) inefficiency in the improvement of hospital admissions for conditions of patients; c) lack of coordinated actions with other companies in order to reduce pollutants in general, their integration in the community and in the country is satisfactory. Proof of this is the level of satisfaction, quite high, of the community. Additionally, A has been one of the best valued companies, positioning itself, often, on top of the 100 best companies in the country. Instead, the company “B” has known a negative insertion in the communities and in the country. Proof of this is quite observable dissatisfaction in the community, which has triggered violent conflicts. In addition, the negativity of the environment impacts caused by the company is too high, which has created some concern to the country. In effect, we came to conclusions that A Company has, to some extent, a set of suitable strategies to the needs of communities and the environmental requirements of the country. On the contrary, the”B” has been characterized by inefficiency in the design of their strategies social responsibility, particularly as regards the establishment and maintenance of a tripartite relationship Company/Government/Communities; the ability to prevent and resolve conflicts Company/Communities; the creation and offering conditions with acceptable quality for the resettlement of communities; the capacity assessment and mitigation of environmental pollution.